RECLAIMING MIND AND SOCIETY IN MIND - Slonimsky, Lynne (PINS-Psychology in Society, 2025)
Miller, Ronald (2011) Vygotsky in perspective. Cambridge: Cambridge University Press. ISBN 978-1-107-00186-2 hbk. Pages xiii + 466 In recent years Lev Vygotsky, the author of Cultural-historical psychology has acquired canonical status in the fields of developmental and educational psychology. Yet, there is a fundamental irony that haunts the works of original thinkers – the more their contribution to knowledge development is recognized in the academy, the greater the tendency to selectively de-locate extracts from their oeuvre and recontextualise them into thematic compilations, collections of selected papers or simplified versions in textbooks. In the process, key concepts tend to become so decontextualized and reified that they lose their meaning or significance, and that which was most generative is lost. In Vygotsky in perspective Ronald Miller proposes that this has been the fate of Vygotsky’s classical text Thinking and speech, in which he offered the most refined and comprehensive exposition of his Cultural-historical theory of consciousness.